Foundations for Nanoscience and Nanotechnology - Peterson,Nils O. (CRC Press,Taylor and Francis Group, 2017)
This is not a book about nanoscience and nanotechnology, but rather an exposition of basic knowledge required to understand these fields. The collection of topics makes it unique, and these topics include: The concept of quantum confinement and its consequences for electronic behaviour (Part II) The importance of surface thermodynamics for activity and interactions of nanoscale systems (Part III) The need to consider fluctuations as well as mean properties in small systems (Part IV) The interaction of light with matter and specific applications of spectroscopy and microscopy (Part V)